Long-term follow-up of surgical treatment of thyroid-associated orbitopathy restrictive strabismus - Savino, Gustavo; Mattei, Roberta; Salerni, Annabella; Fossataro, Claudia; Pafundi, Pia Clara (Frontiers in Endocrinology, 2022)
Objective Thyroid-associated orbitopathy (TAO) is the most frequent cause of extraocular muscle enlargement, with consecutive restrictive strabismus. The main muscles involved are inferior and medial rectus, resulting in horizontal esotropia and/or vertical strabismus. Surgery may either establish or improve binocular single vision. The aim of the present study is to describe long-term follow-up of patients who underwent horizontal or vertical TAO strabismus surgery. Methods This observational retrospective study included 29 patients suffering from either vertical or horizontal TAO strabismus and diplopia, of whom 11 underwent bilateral medial recti muscle recession (Group A) and 18 underwent unilateral inferior rectus muscle recession (Group B). The endpoint of the study was the assessment of changes in deviation angle and diplopia across four time points (baseline, 7 days, 6 months, and 24 months) in each group. Results In Group A, the horizontal deviation angle significantly decreased 7 days after intervention (p < 0.001), without modifications overtime. In Group B, both deviation angles in primary and down-gaze position significantly decreased from baseline, both 7 days after surgery (p < 0.001) and at 6 months (p = 0.040). An overcorrection, with an inversion of vertical deviation angle, was observed across the different time points. Conclusions Horizontal TAO strabismus correction leads to significant improvements of deviation angle and diplopia, with a stable undercorrection overtime. Inferior rectus recession leads to more unstable results, with a trend towards overcorrection limited to the first 6 months after surgery.